Values of Megibung Tradition in Tumbu Traditional Village, Karangasem, Bali: An Ethnopedagogical Study - Ni Putu Ari Krisnayanthi Subyanto; I Wayan Rasna (Universitas Pendidikan Ganesha, 2022)
Bali is known for its culture and customs, one of which is the culture of